2021
DOI: 10.3390/nu13020336
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dietary Animal and Plant Protein Intake and Cardiometabolic Risk Factors—A Cross-Sectional Study in China Health and Nutrition Survey

Abstract: Available data investigating the associations between dietary animal and plant protein intakes and cardiometabolic risk factors (CMRFs) among populations with habitual plant-based diets are heterogenous and limited in scope. The current study was to assess the associations between dietary animal and plant protein intakes and CMRFs, including lipid and lipoprotein profiles, glucose homeostasis biomarkers, low-grade chronic inflammatory biomarker and uric acid in Chinese adults. Data of 7886 apparently healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…A randomized controlled trial in the European population with habitual high intake of protein and animal protein indicated a lower weight regain in high protein intake groups after weight loss, while another trial in the US population with habitual high intake of protein and animal protein indicated no difference in weight maintenance among groups with isocaloric protein (animal or plant sources) or maltodextrin supplements [ 75 , 78 ]. Similar inconsistency presented in observational studies [ 76 , 79 ]. This issue warrants further investigation in China and other transitional countries with habitual low intake of animal foods.…”
Section: Discussionsupporting
confidence: 84%
“…A randomized controlled trial in the European population with habitual high intake of protein and animal protein indicated a lower weight regain in high protein intake groups after weight loss, while another trial in the US population with habitual high intake of protein and animal protein indicated no difference in weight maintenance among groups with isocaloric protein (animal or plant sources) or maltodextrin supplements [ 75 , 78 ]. Similar inconsistency presented in observational studies [ 76 , 79 ]. This issue warrants further investigation in China and other transitional countries with habitual low intake of animal foods.…”
Section: Discussionsupporting
confidence: 84%
“…This study explains that higher consumption of an animal-based diet leads to higher TC levels. A prospective study also shown that animal protein substitution of carbohydrates was positively associated with LDL-cholesterol or TC (51) . However, the notion that animal-based LCD may have a deleterious effect on blood lipids remains speculative.…”
Section: Discussionmentioning
confidence: 93%
“…However, HbA1C was not measured in our study. Fifth, specific patterns of associations have been observed between protein sources and cardiometabolic parameters [ 62 , 63 ]. This aspect was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%